Estilos de crianza y habilidades sociales en adolecentes de la Unidad Educativa Dr. Nicanor Larrea León - Merino Miño, Daisy Elizabeth (2021)
This research is about parenting styles and social skills in adolescents of the Educational Unit “Dr. Nicanor Larrea León”; the aim of this paper is to determine the relationship between the parenting styles and social skills in adolescents. Methodologically this research work has taken a quantitative approach, of non-experimental design, due to the level and correlational scope, by cross-sectional time, of basic and field objectives, the population was a group of teenagers that are from Dr. Nicanor Larrea León Educational Unit with non-probabilistic intentional sample of 86 students (47 men and 39 women). A psychometric test was used to collect in situ data; As the independent variable the ESPA29 Parental Socialization Scale in adolescence made up of 29 items was applied which has allowed to know the perception of the children in front of acts' parents in different occasions, on the other hand, as the dependent variable, The Goldstein Social Skills Scale made up of 50 items was applied. For the statistical analysis, programs such as Excel and the statistical SPSS estadidictic 23 were used, in which it was possible to make evident that there is a significant correlation of ,031 bilateral between parenting styles and social skills.